Synthesis and microstructural characterization of kaolin-polyethylene composites - Agyei-Tuffour, B; Bensah, Y.D; Damoah, L.N.W; Dodoo-Arhin, D; Yaya, A; Nyankson, E; Annan, E; Sarkodee, E; Efavi, J.K (Polymer Composites, 2014)
In this article, the preparation and characterization of kaolin/polyethylene composites are presented. Microstructural characteristics of six different kaolin-polyethylene composites with varying percentage compositions of kaolin and polymer were produced using a modified melt compounding approach, was explored. The characterization methods employed are scanning electron microscopy (SEM), attenuated total reflectance mid Infrared (ATR-MIR), X-ray powder diffraction (XRD), thermogravimetric and differential thermal analysis (TGA-DTA), compressive, flexural strengths and impact resistance analysis. The implications of the results are discussed for the design of kaolin/polymer composites for constructional purposes. POLYM. COMPOS., 35:1507-1515, 2014. © 2013 Society of Plastics Engineers.
Keywords: Composites; Kaolin; Polyethylene; Microstructural